جدلية آية القوامة بين تقرير الوحي والتأويل الحداثيّ - قداري, يمينة; بن سعيدي, سهام (جامعة الوادي - University of Eloued, 2022)
تناولت هذه الدِّراسة حقيقة الجدّل القائم حول آية القوامة، من خلال بيان التّأصيل الشَّرعي لها في محاولة منا التَّعرض لأهم الشُّبهات المثارة من طرف التَّأويل الحداثي واستعراض أهم الرُّدود عليهم، حيث خلصت الدِّراسة إلى اعتصار جملة من النَّتائج كان أهمها أنَّه يوجد فروق جوهريَّة بين اجتهاد الفقهاء والمفسرين في مفهوم القوامة، وأبعادها المقاصديَّة المستندة بعلل التَّشريع، وبين تأويل الحداثيين وأدلتهم العقليَّة المجردة . This research dealt with the reality of the controversy surrounding the verse of guardianship, by identifying the legal rooting of this verse, and exposed the most important suspicions raised by the modernist interpretation and reviewed the most important responses to them. The study concluded that there are fundamental differences between the jurisprudence of jurists and interpreters in the concept of guardianship, and its intended dimensions based on the justifications of the legislation And between the interpretation of the modernists and their abstract rationale evidence.
مقال
Keywords: جدليّة - شبهات القوامة - تقرير الوحي - التأويل الحداثيّ; Dialectic; suspicions; guardianship; jurisprudence interpretations; modern interpretation.